Analisis Pengaruh Implementasi Brand Positioning Terhadap Peningkatan Volume Penjualan Usaha Franchising Kentucky Fried Chicken (Kfc) Di Kota Lhokseumawe - Maimunah, Siti (PASAI, 2013)
This study aims to identify and analyze the effect of the implementation of brand positioning to increase sales volume of business franchising KFC food type on Lhokseumawe. Implementation of brand positioning is the selected product attributes, benefits and product quality, trust and value. Object of research carried out on customers who make a purchase at KFC on Lhokseumawe. The number of samples is as much as 96 respondents. The method of data analysis is a quantitative method, using statistical tools using multiple linear regression analysis by means of SPSS 20. Based on the research, known simultaneously, factor product attributes, benefits and quality of the product and beliefs and values have a significant effect on the increase in sales volume KFC Lhokseumawe. While partially, factor product attributes, benefits and quality of products have a significant effect on the increase in sales volume KFC Lhokseumawe, while trust and value factors had no significant effect on the increase in sales volume KFC Lhokseumawe. Suggestions writer is to increase sales volume in Lhokseumawe KFC, KFC, the company continues to improve factors Lhokseumawe product attributes, benefits and quality of products and increase the beliefs and values that Lhokseumawe KFC sales volume continues to rise.